ECOLOGICAL CRISIS OF TECHNOGENIC CIVILIZATION: RISKS OF THE XXI CENTURY - Drotianko, Liubov (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. Since the late 60's of the twentieth century, scientists and philosophers have talked about the survival of mankind through the irrational activities of people in nature. Since then, a thorough study of the problem of the relationship of man and society to the biosphere began in the natural sciences, in interdisciplinary fields, and in social sciences. In the XXI century, the technological activity of people in a technogenic civilization is significantly expanding beyond the Earth's atmosphere, which encourages a philosophical understanding of the processes of further technologicalization of the biosphere and near space. The aim and tasks Based on the clarification of the meaning of the terms "technogenic civilization" and "technosphere", new aspects of technical and economic activities of mankind and possible risks to nature and society in the XXI century have been identified. Research methodology Methodological means of achieving the stated goal of the study are socio-cultural, systemic and interdisciplinary methodological approaches, the principles of hermeneutics and historicism, as well as the method of cultural and semantic analysis. Research results. The term "technogenic civilization" began to be widely used by methodologists of science to analyze the peculiarities of the development of modern science and technologies based on it from the end of the twentieth century. The meaning of the term "technosphere" correlates with the previous one, clarifying the features of technological activity of mankind in nature. At the beginning of the ХХІ century, new environmental risks are emerging due to the technological development of space. During the development of outer space, humanity has created a man-made shell of the planet, which is poorly consistent with its biological shell. It is important that the development of outer space at the present stage of functioning of the technosphere take place in the interests of all mankind on the principles of anthropocosmism. Discussion The ideas of scientists and philosophers concerning the need for humanity to develop the so-called cosmic or global consciousness are considered. In particular, the article analyzes the views of V.I. Vernadsky, M. M. Moiseev, E. Toffler, E. Moren and others. Their concern about the level of responsibility of people on the planet for the fate of nature is shown, which is why thinkers call for the formation of the Collective Mind and Collective Will (Moiseev). Conclusions. The ecological situation in the Earth's biosphere and near-Earth space can improve if the efforts of international organizations, environmental movements, leading scientists of the world will support the eco-centric approach in the study of the natural environment in its broadest sense and in its technical and technological development. This worldview-methodological approach will contribute to the development of an adequate assessment of existing natural resources and the degree of interdependence of society and the biosphere in general.